THE STUDENTS’ RESPONSES IN IMPLEMENTING LEARNING MEDIA INNOVATION DIGITAL LITERACY BASED ON LOCAL WISDOM FOR ONLINE CLASS TO IMPROVE LISTENING AND WRITING SKILLS AT INFORMATION SYSTEM EDUCATIONAL PROGRAM OF ITB STIKOM BALI - Adrian Fernando Gozali; I Wayan Astu Werdistira (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2023)
The product of Digital Literacy as a Learning Media Innovation for Online Class to Improve Listening and Writing skill of Students in information systems education program at ITB STIKOM Bali has been accomplished, and this research is the continuous of that research especially in the implementation part. Researcher would like to know the effectiveness of the listening product that have been developed. Data was collected by means of documentation, interviews, and questionnaires. The data collected was analyzed quantitatively to determine the average score, where the average score was categorized based on the evaluation table of reference criteria and qualitatively as a description of the score results obtained. The results from the users’ judgement evaluation got the mean score in the aspect content, language, and presentation was 3,6 which belonged to the very good category. The mean score based on the graphic aspect was 3,6 which belonged the very good category. From the students’ perception, the mean score was 3,75 which belonged the very good category. It showed that the media developed by researcher was very good and appropriate used for improving listening skill of students in information systems education program at ITB STIKOM Bali.